(-6)-b+2c=0

Simple and best practice solution for (-6)-b+2c=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-6)-b+2c=0 equation:


Simplifying
(-6) + -1b + 2c = 0
-6 + -1b + 2c = 0

Solving
-6 + -1b + 2c = 0

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + -1b + 6 + 2c = 0 + 6

Reorder the terms:
-6 + 6 + -1b + 2c = 0 + 6

Combine like terms: -6 + 6 = 0
0 + -1b + 2c = 0 + 6
-1b + 2c = 0 + 6

Combine like terms: 0 + 6 = 6
-1b + 2c = 6

Add '-2c' to each side of the equation.
-1b + 2c + -2c = 6 + -2c

Combine like terms: 2c + -2c = 0
-1b + 0 = 6 + -2c
-1b = 6 + -2c

Divide each side by '-1'.
b = -6 + 2c

Simplifying
b = -6 + 2c

See similar equations:

| 2z+8=7z-19 | | 64/80 | | 3-9c=7(6) | | 2/3-5=1 | | W+2w+w+2w=450 | | 17x+5=3(4) | | 6x+3x+4=76 | | -p^2-9p-8=0 | | 2(2x+1)+(-3)+(-6)=3x+(-3)+x+8 | | 4(3-x)=4x | | 11m=-33+8z | | 2(2x+1)+(-3)+(-6)= | | 2(2x+1)+(-3)+(-6)=x | | 2n-7=27 | | a+2b+3c=13 | | 5a+56=7(8) | | 8x-3x-7=38 | | -5(3x+1)-14=10(x+2)-2x+1 | | 4x-2=13-2x | | -5(3x+1)=10(x+2)-2x+1 | | 8-4m+5-6m= | | 37=X+3X-4 | | 15c-8c=20c-13 | | Y=4-3(1.33) | | 4n/5-1/5=2n/5 | | 2.95*1=4x | | 11.97=x/1.2 | | 2.95*4=1x | | 3(2x+1)=7x | | (2x-pi/4)=-1 | | 3y+8=2y-2 | | 20=4y+8x |

Equations solver categories